2016
DOI: 10.1093/gji/ggw364
|View full text |Cite
|
Sign up to set email alerts
|

Teleseismic depth estimation of the 2015 Gorkha−Nepal aftershocks

Abstract: The depth of 61 aftershocks of the 2015 April 25 Gorkha, Nepal earthquake, that occurred within the first 20 d following the main shock, is constrained using time delays between teleseismic P phases and depth phases (pP and sP). The detection and identification of these phases are automatically processed using the cepstral method developed by Letort et al., and are validated with computed radiation patterns from the most probable focal mechanisms. The events are found to be relatively shallow (13.1 ± 3.9 km). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…We observe that most of the depths of deeper events-presumably associated with the MHT-match the depth of the MHT shear zone as determined by Duputel et al (2016). We further show that, in general, the depths of the aftershocks are close to those obtained by Letort et al (2016) using time delays between teleseismic P and depth phases, confirming an average deepening of the events from west to east (from 15 to 18 km).…”
Section: O N C L U S I O N Ssupporting
confidence: 78%
See 3 more Smart Citations
“…We observe that most of the depths of deeper events-presumably associated with the MHT-match the depth of the MHT shear zone as determined by Duputel et al (2016). We further show that, in general, the depths of the aftershocks are close to those obtained by Letort et al (2016) using time delays between teleseismic P and depth phases, confirming an average deepening of the events from west to east (from 15 to 18 km).…”
Section: O N C L U S I O N Ssupporting
confidence: 78%
“…Figure S3. Depth differences between Letort et al (2016) catalogue and ours for 25 commons events. Note the linear bias with depth.…”
Section: Automatic Analysis Of the Gorkha Aftershocks S U P P O Rt I mentioning
confidence: 62%
See 2 more Smart Citations
“…Moreover, some recent studies have found that the hypocenters of most of the earthquakes in Nepal are located at depths ranging between 0 and 30 km (Pandey et al, ; Priestley et al, ). In addition, hypocenter relocation results from a nearby broadband seismic array found that the focal depths for the Gorkha earthquake sequence ranged primarily between 10 km and 20 km (Adhikari et al, ; Bai et al, ; Letort et al, ). Thus, in this analysis, the average focal depth of 15 km is assigned as a constant depth for all the source models.…”
Section: Methodsmentioning
confidence: 99%